Differences in counselors' career outputs in view of licensure status in Malaysia - Ooi, Pei Boon; Wan Jaafar, Wan Marzuki; Baba, Maznah (International Association of Computer Science and Information Technology (I A C S I T), 2016)
Malaysia is a rapidly developing country. In the last decade, the availability of counseling services has been getting progressive attention and there arises the question of who govern the standard and practice of the counseling service providers. In Malaysia, school counselors are encouraged to register under the Malaysia Board of Counselor which is subjected to the Counselors Act 1998 or Act 580 of the Laws of Malaysia. This paper aimed to study and examine the licensure status of Malaysia school counselors and its’ relation with their career outputs. Three hundred and forty five secondary school counselors in Malaysia responded via paper and online survey. The result shows counselors who are registered with the Malaysia Board of Counselor demonstrated higher levels of job satisfaction, career success, professional commitment and self-perceived employability. The reasons of not registered were also explored and discussed in this paper. The recommendation and suggestions for future policy development and governance were discussed.